PENGARUH KUALITAS SDM, BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA KARYAWAN NON ASN DI UPT PUSKESMAS MANGARAN - Hasanah, Mariyatul; Tulhusnah, Lusiana; Fandiyanto, Randika (Fakultas Ekonomi dan Bisnis, 2024)
Human Resources (HR) is essential in helping institutions achieve their goals and actions. Human resources are one of the elements that determine the success or failure of a company in achieving its goals. This study aimed to analyze and test the effect of HR Quality, Organizational Culture, and Work Motivation on Employee Performance with Job Satisfaction as an Intervening Variable. This study's target population wwere the employees of the technical implementation unit of Mangaran public health center (UPT Puskesmas Mangaran) who became respondents, totaling 60 people. This sampling technique is simple random sampling. The study's data analysis and hypothesis testing used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of direct influence hypothesis testing using the Smart PLS 3.0 application show that HR quality has a significant positive effect on job satisfaction, organizational culture has a significant positive effect on job satisfaction, work motivation has a significant positive effect on job satisfaction, HR quality has a significant negative effect on performance, organizational culture has a positive but insignificant effect on performance, work motivation has a positive and insignificant effect on performance, job satisfaction has a significant positive effect on performance. Then, the indirect effect hypothesis test results show that the variable HR quality on performance through job satisfaction has a significant positive effect, organizational culture on performance through job satisfaction has a significant positive effect, and work motivation on performance through job satisfaction has a significant positive effect.